Optimization and Energy Management in Smart Grids (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Special Issue focuses on bringing together innovative developments and synergies in new control strategies and power grids.Other potential topics include but are not limited to the following: Energy storage devices; More on-site power generation; Flexible demand response; Real-time distribution and customer data; Real-time price signals; Smart distribution system and processes; Better customer information, choices, and tools; Smart metering experiences.